1945
DOI: 10.1172/jci101624
|View full text |Cite
|
Sign up to set email alerts
|

Cold Agglutinins. Ii. Cold Isohemagglutinins in Primary Atypical Pneumonia of Unknown Etiology With a Note on the Occurrence of Hemolytic Anemia in These Cases

Abstract: In the preceding paper ( 1), there was presented a summary of the maximum titers of cold agglutinins found in 1069 cases of a variety of conditions, including the various infections of the respiratory tract that are commonly encountered in this vicinity. Significant titers (in dilutions greater than 20) were Methods. The method used in the tests for cold agglutins was given in detail in the preceding paper (1). For the present study, the specimens of venous blood were all collected under sterile precautions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1945
1945
1974
1974

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…Interpretation of the data is complicated by the present lack of knowledge of the nature of these fluorescent-stainable antibodies. Patients with primary atypical pneumonia may develop a variety of abnormal serologic reactions during convalescence: agglutinins for group 0 erythrocytes in the cold; agglutinins for streptococcus MG; complement-fixing reactions for various heterologous tissue antigens; and even false serologic tests for syphilis (8)(9)(10)(11)(12)(13)(14)(15). Liu and associates, by means of cross-absorption experiments, demonstrated that the fluorescent-stainable antibodies are distinct from cold hemagglutinins and streptococcus MG agglutinins (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpretation of the data is complicated by the present lack of knowledge of the nature of these fluorescent-stainable antibodies. Patients with primary atypical pneumonia may develop a variety of abnormal serologic reactions during convalescence: agglutinins for group 0 erythrocytes in the cold; agglutinins for streptococcus MG; complement-fixing reactions for various heterologous tissue antigens; and even false serologic tests for syphilis (8)(9)(10)(11)(12)(13)(14)(15). Liu and associates, by means of cross-absorption experiments, demonstrated that the fluorescent-stainable antibodies are distinct from cold hemagglutinins and streptococcus MG agglutinins (5).…”
Section: Discussionmentioning
confidence: 99%
“…Using a modification of the fluorescent antibody technique of Coons and Kaplan (4), Liu, Eaton and Heyl have provided both a means of localizing the antigens in the chick embryo and a method by which sera can le examined for fluorescent-stainable antibodies to Eaton's agent (3,5). Additional isolations of Eaton's agent from patients and demonstrations of fluorescent-stainable antibodies to it have been reported by Cook (6) and Chanock (7) and their associates, confirming and extending the observations of Eaton and Liu. The specificity of this fluorescent antibody reaction in terms of the etiology of the disease has been questioned (8), however, since patients with primary atypical pneumonia may develop a number of nonspecific serologic responses (9)(10)(11)(12)(13)(14)(15). Primary atypical pneumonia produced under experimental conditions in man would provide an ideal situation for comparison of these various serologic tests.…”
mentioning
confidence: 99%
“…The sera used in the present study were obtained from 3 types of individuals: (1) a number of patients with primary atypical pneumonia that were included in the previous study (5); (2) patients with hemolytic anemia associated with cold agglutinins but without atypical pneumonia (these cases have also been referred to in the previous studies (6)); and (3) patients and members of the hospital staff who were free of respiratory disease and of blood dyscrasia. Venous blood was drawn and cell-free serum was obtained by centrifugation after the clotted blood had been warmed at 370 C.…”
Section: Methodsmentioning
confidence: 99%
“…The titers were read as the reciprocal of the highest final dilution of serum giving floccular agglutination. The method used in the cold hemagglutination tests is described in a previous paper (3).…”
Section: Methodsmentioning
confidence: 99%